2007
DOI: 10.1021/ie061630y
|View full text |Cite
|
Sign up to set email alerts
|

Using a Fiber-Optic Probe for the Measurement of Volumetric Expansion of Liquids

Abstract: A fiber-optic probe is developed for the fast, in-situ measurement of volumetric expansion of multiphase and multicomponent systems. An experiment with the binary mixtures of CO 2 -toluene and CO 2 -ethanol was conducted to demonstrate the usefulness of the fiber-optic probe in accurately tracking the isothermal volumetric expansion as a function of pressure. In the 1-L autoclave that has been used, the probe was shown to detect the liquid level height within a precision of 0.35% of the total height of the ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Apart from measuring phase boundaries, we have also demonstrated that the FOR method can be used for monitoring the volumetric expansion of organic solvents with scCO 2 by immersing the end of the optic fibre into liquid (Avdeev et al 2004). Recent work by Dudukovic and his co-workers (Mueller et al 2007) has also reported a fibre-optic approach for measuring volumetric expansion, in which a multi-mode optical fibre is employed as a position sensor for monitoring the position of the meniscus between the liquid and the CO 2 phase.…”
Section: The Fibre-optic Reflectometermentioning
confidence: 90%
See 1 more Smart Citation
“…Apart from measuring phase boundaries, we have also demonstrated that the FOR method can be used for monitoring the volumetric expansion of organic solvents with scCO 2 by immersing the end of the optic fibre into liquid (Avdeev et al 2004). Recent work by Dudukovic and his co-workers (Mueller et al 2007) has also reported a fibre-optic approach for measuring volumetric expansion, in which a multi-mode optical fibre is employed as a position sensor for monitoring the position of the meniscus between the liquid and the CO 2 phase.…”
Section: The Fibre-optic Reflectometermentioning
confidence: 90%
“…Recent work by Dudukovic and his co-workers (Mueller et al 2007) has also reported a fibre-optic approach for measuring volumetric expansion, in which a multi-mode optical fibre is employed as a position sensor for monitoring the position of the meniscus between the liquid and the CO 2 phase.…”
Section: The Fibre-optic Reflectometermentioning
confidence: 99%
“…The method of optical fiber probes was developed in the second half of the 20th century [34]. Recent studies dealt with single-fiber probes using the same fiber as emitter and receiver [35][36][37][38][39]. On the contrary, the current work is based on a twofiber optical sensor where an emitting and a receiving fiber are applied separately.…”
Section: Optical Fiber Sensorsmentioning
confidence: 99%
“…In-situ fiber optic spectroscopy provides a solution to this challenge. It is gaining attention in the field of heterogeneous catalysis [17][18][19][20][21][22][23][24][25], continuous process analyses [26][27][28][29][30], batch process analyses [31,32] and clinical applications [33,34]. For example, a fiber optic based UV-vis CCD spectrometer was employed for the determination of nickel breakthrough in an ion-exchange column [26].…”
Section: Introductionmentioning
confidence: 99%